From Research to Community Impact: Implementing Liquid Complementary Fertilizer Innovation to Promote Sustainable Agriculture in Narumonda III Village - Rikson Asman Fertiles Siburian; Kerista Tarigan; Tulus Joseph Herianto; Andrew Satria Lubis; Jonathan Liviera Marpaung (Talenta Publisher, 2026)
Rural agricultural communities in Indonesia face persistent challenges, including dependence on chemical fertilizers, declining soil quality, and increasing production costs. Limited adoption of research-based innovations further constrains sustainable farming practices. This community service program aimed to implement and evaluate a liquid complementary fertilizer innovation through a participatory Focus Group Discussion (FGD) approach in Narumonda III Village, Toba Regency. The program applied participatory methods consisting of pre-test and post-test assessments, FGD sessions, farmer training, field demonstrations, and collaboration with an industry partner, with active community involvement throughout the process. Results showed improved farmer knowledge of sustainable fertilization and nutrient management, along with positive acceptance of the liquid complementary fertilizer. Participants recognized its potential to reduce input costs, improve soil quality, and enhance crop productivity. The program also strengthened collaboration among the university, local community, and industry partner, supporting effective knowledge transfer. These findings indicate that FGD-based community engagement is effective in disseminating agricultural innovation and supporting sustainable rural development.